Microorganisms in foods 8 use of data for assessing process control and product acceptance (Microorganisms in foods, 2011)
aContinuing the ICMSF series, Microorganisms in Foods 8provides practical guidance on appropriate testing of food processing environments, processing lines, shelf life and finished product to enhance the safety and microbiological quality of the food supply. Part I, Principles of Using Data in Microbial Control, summarizes the principles of Microorganisms in Foods 7: Microbiological Testing in Food Safety Management (2002), which illustrates how HACCP and Good Hygienic Practices (GHP) provide greater assurance of safety than microbiological testing, and also identifies circumstances where microbiological testing may play a useful role. Part II, Applications of Principles to Product Categories, updates and expands Part II of Microorganisms in Foods 2: Sampling for Microbiological Analysis: Principles and Specific Applications (1986) and builds on Microorganisms in Foods 6: Microbial Ecology of Food Commodities (2nd edition, 2005) with recommended tests and specific criteria for 19 food product categories to evaluate the effectiveness of controls. Microorganisms in Foods 8 is intended for anyone using microbiological testing or engaged in setting microbiological criteria including government, food processors and the customers they supply. This book provides actionable information for food quality assurance professionals, food microbiologists, food technologist, veterinarians, public health workers and regulatory officials. This peer reviewed book was prepared by the International Commission on Microbiological Specifications for Foods (ICMSF), with assistance from a limited number of consultants. The ICMSF was formed in response to the need for internationally acceptable and authoritative guidance on microbiological limits for foods in international commerce. Currently the membership consists of 17 food microbiologists and public health professionals from eleven countries, drawn from government, universities, and food processing and related industries. Also available Microorganisms in Foods 7: Microbiological Testing in Food Safety Management, 2002 (978-0-306-47262-6) Microorganisms in Foods 6: Microbial Ecology of Food Commodities, 2nd edition 2005 (978-1-4419-3465-9) Microorganisms in Foods 5: Characteristics of Microbial Pathogens, 1996 (978-0-412-47350-0)